Dolutegravir resistance in sub-Saharan Africa: should resource-limited settings be concerned for future treatment? - Kamori, Doreen; Barabona, Godfrey (Frontiers in Virology, 2023)
In Sub-Saharan Africa (SSA) the burden of non-nucleoside reverse transcriptase inhibitors (NNRTI) HIV drug resistance (HIVDR) has been high over the years. Therefore, in 2018 the World Health Organization (WHO) recommended the use of integrase strand transfer inhibitor (INSTI), dolutegravir (DTG)-based regimen as the default first-line antiretroviral therapy (ART) in countries in SSA. The scale-up of DTG-based regimens in SSA has gained significant momentum since 2018 and continues to expand across multiple countries in recent years. However, whether DTG robustness experienced in the developed world will also be achieved in SSA settings is still an important question. Evidence generated from in vitro and in vivo studies suggests that the emergence of DTG HIVDR is HIV-1 subtype dependent. These findings demonstrate that the extensive HIV-1 diversity in the SSA can influence DTG effectiveness and the emergence of drug resistance. In addition, the programmatic approach to the transition to DTG adopted by many countries in the SSA region potentially exposes individuals to DTG functional monotherapy which is associated with the emergence of DTG resistance. In this mini-review, we describe the current trends of the effectiveness of DTG as reflected by viral suppression and DTG resistance. Furthermore, we explore how HIV-1 diversity and the programmatic approach in SSA could shape DTG effectiveness and DTG HIVDR in the region.